To seek or not to seek: The interplay of academic help seeking, concealment and achievement - Villavicencio, Felicidad T. (Animo Repository, 2006)
The purpose of this study was to examine the interplay of motivational factors, help seeking, concealment, and academic achievement measured in terms of GPA. Different competing models were tested to see the influence of each other using hierarchical regression analysis. First, the influence of motivational factors on achievement and help seeking/concealment behaviour was tested; second, the help seeking and concealment behaviour were also entered in the analysis. A total of 215 freshmen college engineering students enrolled in Algebra participated in this study. GPA was significantly predicted by two motivational variables: self-efficacy for learning and performance (expectancy component) and test anxiety (affective component). Concealment behaviour was found to be a significant predictor of GPA. On the other hand, GPA was found to be a significant predictor of concealment behavior together with extrinsic goal orientation (value component) and test anxiety (affective component). Discussion was focused On those circumstances that are related to help seeking behavior by highlighting the important role that motivational factors play in students' academic help seeking behavior and achievement.